Decreased Cerebral Amyloid-β Depositions in Patients With a Lifetime History of Major Depression With Suspected Non-Alzheimer Pathophysiology - Wu, Kuan-Yi; Lin, Kun-Ju; Chen, Chia-Hsiang; Liu, Chia-Yih; Wu, Yi-Ming; Chen, Cheng-Sheng; Yen, Tzu-Chen; Hsiao, Ing-Tsung (Frontiers in Aging Neuroscience, 2022)
Cerebral amyloid-β (Aβ) depositions in depression in old age are controversial. A substantial proportion of individuals with late-life major depressive disorder (MDD) could be classified as having suspected non-Alzheimer disease pathophysiology (SNAP) by a negative test for the biomarker amyloid-β (Aβ-) but positive neurodegeneration (ND+). This study aimed to evaluate subthreshold Aβ loads in amyloid-negative MDD, particularly in SNAP MDD patients. This study included 46 amyloid-negative MDD patients: 23 SNAP (Aβ-/ND+) MDD and 23 Aβ-/ND- MDD, and 22 Aβ-/ND- control subjects. All subjects underwent 18F-florbetapir PET, FDG-PET, and MRI. Regions of interest (ROIs) and voxel-wise group comparisons were performed with adjustment for age, gender, and level of education. The SNAP MDD patients exhibited significantly deceased 18F-florbetapir uptakes in most cortical regions but not the parietal and precuneus cortex, as compared with the Aβ-/ND- MDD and control subjects (FDR correction, p<0.05). No correlations of neuropsychological tests or depression characteristics with global cortical uptakes, but significant positive correlations between cognitive functions and adjusted hippocampal volumes among different groups were observed. The reduced Aβ depositions in the amyloid-negative MDD patients might be attributed mainly to the SNAP MDD patients. Our results indicated that meaningfully low amounts of subclinical Aβ might contain critical information on the non-amyloid-mediated pathogenesis.